Predicting resistance to biological therapy using human leukocyte antigen genes in patients with inflammatory bowel disease - Ângela Domingues; Ana Carvalho; António Martinho; Caroline Soares; Diana Martins; Paula Sousa; Ricardo Araújo; Eugénia Cancela; Américo Silva; Paula Ministro (Therapeutic Advances in Gastroenterology)
Background: The efficacy of anti-tumor necrosis factor (TNF) therapy in inflammatory bowel disease (IBD) is often compromised by the development of antidrug antibodies. In this setting, the human leukocyte antigen (HLA)-DQA1*05 allele has been significantly associated with the formation of antidrug antibodies to anti-TNF agents, loss of response, and treatment discontinuation. Objectives: We aimed to determine whether HLA-DQA1*05 genotyping is associated with clinically meaningful outcomes in patients with IBD. Design: A single-center, prospective study was conducted on patients with IBD who were naïve to biological treatment and were initiating therapy with anti-TNF agents, vedolizumab, or ustekinumab. Methods: All patients were genotyped for HLA-DQA1*05. The primary endpoint was the achievement of a composite outcome encompassing clinical, biochemical, and endoscopic remission at week 54, stratified by HLA-DQA1*05 status. The secondary endpoints included the evaluation of therapeutic persistence and the development of antidrug antibodies. Results: One hundred biologic-naïve patients with IBD initiating biological therapy were included in the study (72 on anti-TNF, 18 on vedolizumab, and 10 on ustekinumab); of these, 43% were HLA-DQA1*05 positive. The presence of the HLA-DQA1*05 allele was not associated with worse clinical outcomes, defined as the composite of clinical, biochemical, and endoscopic remission at week 54, in patients treated with anti-TNF agents, vedolizumab, or ustekinumab. In addition, no significant correlation was observed between the HLA-DQA1*05 genotype and reduced therapy persistence or increased immunogenicity. Conclusion: In our cohort of patients with IBD, the HLA-DQA1*05 genotype was not associated with a higher risk of treatment cessation or worse clinical outcomes. Trial registration: Can we rely on HLA to predict resistance to biological therapy in patients with IBD? URL: https://clinicaltrials.gov/study/NCT05040854?cond=Can%20we%20rely%20on%20HLA&rank=1 . Registration number: NCT05040854 (clinicaltrials.gov).